Comparison of Frequency of Mitral Regurgitation in Anterior Vs Inferior Wall Myocardial Infarction - Mumtaz, Abdullah; Tariq, Ali Bin; Siddique, Aamir; Tawwab Khan, Rao Shahzad Abdul; Habiburahman, .; Sattar, Abdul (Biological and Clinical Sciences Research Journal, 2025)
Mitral regurgitation (MR) is a common mechanical complication of acute myocardial infarction (MI) that significantly impacts morbidity and mortality. Objective: To determine and compare the frequency of mitral regurgitation in patients with anterior versus inferior wall myocardial infarction and to assess its association with echocardiographic and clinical parameters. Methodology: This Descriptive Cross-sectional study was conducted at the Cardiology Department of Ch. Pervaiz Elahi Institute of Cardiology, Wazirabad, from 10 October 2024 to 10 April 2025. A total of 75 patients with acute ST-elevation myocardial infarction were enrolled using non-probability consecutive sampling. Among them, 36 had anterior wall MI and 36 had inferior wall MI. All participants underwent electrocardiography and echocardiography upon admission, followed by a repeat echocardiogram after 72 hours to assess the presence and severity of MR. Baseline parameters such as age, gender, blood pressure, HbA1c, serum creatinine, Pro-BNP levels, and ejection fraction were recorded. Results: The mean age of the study population was 58.6 ± 10.4 years, with 64% males and 36% females. Mitral regurgitation was observed in 27 patients (36%), including 18 cases of mild, 7 of moderate, and 2 of severe MR. MR was significantly more frequent in inferior wall MI (61.1%) than in anterior wall MI (13.9%) (p = 0.001). The mean ejection fraction was lower in anterior wall MI (43.1 ± 7.8%) compared to inferior wall MI (49.5 ± 9.1%) (p = 0.02). MR was more common in patients with right coronary artery involvement, severe vessel occlusion (>75%), elevated Pro-BNP levels, and reduced ejection fraction (<45%) (p < 0.05). Conclusion: It is concluded that mitral regurgitation occurs significantly more frequently in inferior wall myocardial infarction compared to anterior wall infarction, mainly due to ischemic involvement of the posteromedial papillary muscle supplied by the right coronary artery. Early echocardiographic detection and management of MR in inferior wall MI patients are essential to prevent hemodynamic deterioration and improve overall clinical outcomes.